Hyperibone J exerts antidepressant effects by targeting ADK to inhibit microglial P2X7R/TLR4-mediated neuroinflammation - Ting Li; Yawei Li; Jinhu Chen; Miaomiao Nan; Xin Zhou; Lifang Yang; Wenjun Xu; Chao Zhang; Lingyi Kong (Journal of Advanced Research)
Introduction: The antidepressant properties of Hypericum species are known. Hyperibone J, a principal component found in the flowers of Hypericum bellum, exhibited in vitro anti-inflammatory effects. However, the antidepressant effects and mechanisms of Hyperibone J remain to be elucidated. Adenosine kinase (ADK) is upregulated in epilepsy and depression and has been implicated in promoting neuroinflammation. Objectives: This study aimed to explore the impact of Hyperibone J on neuroinflammation-mediated depression and the mechanism underlying this impact. Methods: This study employed acute and chronic in vivo depression models and an in vitro LPS-induced depression model using BV-2 microglia. The in vivo antidepressant efficacy of Hyperibone J was assessed through behavioral assays. Techniques such as RNA-seq, western blot, qPCR and ELISA were utilized to elucidate the direct target and mechanism of action of Hyperibone J. Results: Compared with the model group, depression-like behaviors were significantly alleviated in the Hyperibone J group. Furthermore, Hyperibone J mitigated hippocampal neuroinflammation and neuronal damage. RNA-seq suggested that Hyperibone J predominantly influenced inflammation-related pathways. In vitro experiments revealed that Hyperibone J reversed the LPS-induced overexpression and release of inflammatory factors. Network pharmacology and various molecular biology experiments revealed that the potential binding of Hyperibone J at the ASN-312 site of ADK diminished the stability and protein expression of ADK. Mechanistic studies revealed that Hyperibone J attenuated the ADK/ATP/P2X7R/Caspase-1-mediated maturation and release of IL-1β. The study also revealed a significant correlation between Tlr4 expression and depression-like behaviors in mice. Hyperibone J downregulated ADK, inhibiting Tlr4 transcription, which in turn reduced the phosphorylation of NF-κB and the subsequent transcription of Nlrp3, Il-1b, Tnf, and Il-6. Conclusion: Hyperibone J exerted antineuroinflammatory and antidepressant effects by binding to ADK in microglia, reducing its expression and thereby inhibiting the ATP/P2X7R/Caspase-1 and TLR4/NF-κB pathways. This study provides experimental evidence for the therapeutic potential of Hypericum bellum.